Religious aspects of pottery in the Early Iron Age burial rite - Potrebica, Hrvoje (Array, 2004)
The paper summarizes different roles that pottery vessels may assume in cult practice related to burials in the Early Iron Age (the Hallstatt Culture). The pottery vessels are too often taken out of the original context (i.e. grave assemblage) and exposed to classic typological-chronological analysis. In many cases such approach resulted in misinterpretation which often had consequences to the understanding of the burial as a whole. The pottery used in cult activity connected to the burial and often found outside actual boundaries of the grave is also in many cases ignored or interpreted as less important material. There are three categories of pottery vessels that could be connected to the burial ritual. The first is vessel used as container for the remains of the deceased. In most cases it is some kind of urn used after cremation of the deceased, but there is also possibility of skeletal burials in large pottery vessels. The second class consists of vessels used by the community in the cult practice related to ritual. Those vessels may be located in the grave as the final result of burial ritual, but they could also indicate some religious practice outside the grave, prior or after the burial. The third class comprises of pottery vessels or objects that were intended to be used by the deceased in the afterlife, or they form some kind of symbolic/religious structure used in communication between the living community and their mythological counterpart. All there categories of pottery may be produced specially for the purpose of specific burial or those objects may have some other original use. This paper will try to illustrate these classes with the burial practice of the Hallstatt Culture and raise some important conceptual issues connected to their interpretation.